Transcriptomic modifiers of the cognitive consequences of apolipoprotein E. (1st February 2022) - Seto, Mabel; Dumitrescu, Logan; Mahoney, Emily R.; Hansen, Shania L; Khan, Omair A.; Liu, Dandan; De Jager, Philip L; Petyuk, Vladislav A; Schneider, Julie A.; Bennett, David A.; Gifford, Katherine A.; Jefferson, Angela L.; et al.
Abstract: Background: APOE ‐ε4 is the strongest common genetic risk factor for Alzheimer's disease (AD) and contributes to worse cognition. However, many carriers of the APOE ‐ε4 allele remain cognitively normal throughout life, suggesting resilience factors may exist that protect the brain. We leverage a unique statistical design to identify modifiers of APOE effects on cognition by first discovering gene modifiers leveraging RNA sequencing (RNAseq) from whole blood and then replicating any observed modifiers with brain RNAseq from an independent cohort. Transcripts that modify the association between APOE and cognitive decline may highlight pathways of risk or resilience that could be repurposed as targets for intervention. Method: Cognition, RNAseq from whole blood, and APOE genotype were obtained from 336 individuals from the Vanderbilt Memory and Aging Project (VMAP; mean(SD) age=72.9(7.3), % male=59, % mild cognitive impairment=39). RNAseq data were quantile normalized and batch corrected. Regression and mixed‐effects regression models assessed the interaction between baseline gene expression and APOE ‐ε4 or APOE ‐ε2 positivity on both baseline and longitudinal decline in memory, adjusting for baseline age and sex. Results were replicated using bulk dorsolateral prefrontal cortex RNAseq data in 618 participants from the Religious Orders Study/Memory and Aging Project (ROS/MAP). Results were corrected for multiple comparisons (60, 669 genes) using the false discovery rate method. Results: Cross‐sectionally, RNASE6 interacted with APOE‐ ε4 status on memory (β=‐1.16, p=4.35x10 ‐8 ) whereby low RNASE6 expression was associated with better memory performance at baseline among APOE‐ ε4 carriers, but high RNASE6 expression was associated with worse memory performance among APOE‐ ε4 carriers (Figure 1). These results replicated in brain RNAseq data from ROS/MAP (β=‐0.2, p=0.0009, Figure 2). There were no significant interactions longitudinally or with APOE ‐ε2. Conclusion: RNASE6 encodes a protein involved in innate immunity, including antimicrobial and antiviral activity. It has not been previously associated with AD or AD‐related cognitive decline, though it has been identified in a co‐expression network module with other inflammatory genes, such as TYROBP ( DAP12 ), previously linked to AD. Together, these data implicate neuroinflammatory regulation in cognitive decline, and suggest that innate immune signaling may contribute to the regulation of resilience and susceptibility to AD among APOE‐ ε 4 carriers.